Optimization of Ultimate Tensile Strength with DOE Approach for Application FSW Process in the Aluminum alloys AA6061-T651 & AA7075 -T651 (Fracture and Structural Integrity, 2021)
As it is imperative to control the materials development processes well, in parallel, it will be necessary to constantly adapt very efficient assembly methods. Friction stir welding makes it much easier for us to fusion the aluminum alloys like AA6061-T651 and AA7075 -T651. But we noted the difficulty of containing its many parameters such as the welding speed, the rotation speed and the type of pin used during the operation to optimize mechanical properties and in particular to obtain high rupture strength with the tensile test. This why in this paper we treat carefully this process in order to define it drastically, by using the design of experiment method which is an original approach that resides in the possibility of interpretation of experimental results with a minimal effort on the experimental level whichever generates the minimization of the necessary number of experiments and allows a saving in time and in financial cost.
Keywords: FSW welding; Rupture strength; Design of experiment; optimization UTS